CURRENCY MULTIPOLARITY IN THE SYSTEM OF GLOBAL FINANCE - O. Bulkot (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The key determinants for defining and development of international position of currency are given. The main tendencies of composition of international reserves by currency component are determined. The parameters of main international reserve currencies are comparatively analyzed. The key modern tendencies in evolution of the system of global finance and the international monetary system in particular are examined.